The future relations between the majority and minority religious groups, viewed from indonesian contemporary perspective: a case study of the coexistence of Muslims and the Towani Tolotang in Amparita, South Sulawesi - Jubba, Hasse; Pabbajah, Mustaqim; Prasodjo, Zainuddin H; Qodir, Zuli (Penerbit Universiti Kebangsaan Malaysia, 2019)
The topic of relations of several religious groups in the world from different perspectives has been a hot issue among researchers and stakeholders. This article addresses the future relations between the majority and minority religious groups, particularly a case study of Bugis Muslims and Bugis Hindus known as Towani Tolotang who live in a harmonious life in South Sulawesi seen from Indonesian contemporary perspective. The present article is based on our research conducted in 2017 and 2018. The results show that Muslim majority and Hindu minority have been living in a dynamic and harmonious life because they have shared similar Bugis cultural background and tradition. In addition, the honesty of Bugis Muslims towards Bugis Hindus has contributed to a conducive living atmosphere. In addition, the existence of equality for the socio-politico status and economic endeavour for the Muslim majority and Hindu minority has brought them into a good social life. So, both communities may enjoy a long period of peaceful and prosperous coexistence in Indonesian modern life.